2010
DOI: 10.12693/aphyspola.117.799
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Thin Films β-Al-Mg Obtained Using PLD Technique

Abstract: In this work, the pulsed laser deposition (PLD) technique was used to grow AlMg thin films from a β-Mg 2 Al 3 target with nominal composition: 39.09 at.% Mg and 60.91 at.% Al. The paper presents the study of β-Mg 2 Al 3 thin films deposited using the pulsed laser deposition technique. AlMg thin films were prepared on Si (400) substrates and deposited by means of using a QS-Nd:YAG laser (λ = 266, 355 nm). Samples were prepared with laser fluence (1.1 J/cm 2 and 1.6 J/cm 2 ) and at two different substrate (Si) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In fact, most droplets reach the substrate in a molten state and are quenched as flat discs on the substrate. Our previous investigations [5,8] showed that these droplets owned the higher concentration of aluminium. The transmission electron microscopy is the suitable technique for the calculation of the thin films thickness.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In fact, most droplets reach the substrate in a molten state and are quenched as flat discs on the substrate. Our previous investigations [5,8] showed that these droplets owned the higher concentration of aluminium. The transmission electron microscopy is the suitable technique for the calculation of the thin films thickness.…”
Section: Resultsmentioning
confidence: 89%
“…The film Al-Mg film was prepared on Si (100) at 200 C (T s -substrate temperature) while Al-Mg-Ni multilayer on AZ91D alloy at 20 C (T s ). These process parameters assured the high deposition rates and the nanocrystalline structure of the films [5][6][7][8]. The details of the laser depositions were showed in previous paper [5].…”
Section: Materials and Experimental Proceduresmentioning
confidence: 82%
See 2 more Smart Citations